The Myotei dialogues : a Japanese Christian critique of native traditions - Fabian, active 1583-1607.; Baskind, James.; Baskind, James.; Bowring, Richard John, 1947-; Breen, John, 1956-; Krämer, Hans Martin. (Numen Book Series, 2015)
The Myōtei Dialogues is the first complete English translation one of the most important works of early Japanese Christianity. Fukansai Habian's Myōtei mondō (1605) presents a sharp critique of the three main Japanese traditions, Buddhism, Shintō, and Confucianism, followed by an explanation of the main tenets of Christianity specifically aimed at a Japanese audience. Written by a convert, it is of importance not merely because it shows us how the Christian message was presented by a Japanese to other Japanese, but also for what it reveals about the state of the three native traditions at the beginning of the seventeenth century.